Pengaruh Pertumbuhan Penjualan, Leverage Operasi, dan Profitabilitas terhadap Struktur Keuangan - Elyzabet Indrawati Marpaung (Jurnal Akuntansi, 2010)
The objective of this research is to know the influence of sales growth , degree of operating leverage, and profitability on the financial structure both simultaneously and partially. Purposive sampling is used as sanpling technique. The sample is taken from LQ45 index constituent company for the year of 2006 until 2008. The data are analyzed using Multiple Regression Analysis. The result on this research shows that sales growth, degree of operating leverage, and profitability have significant influence on the financial structure. Sales growh and profitability have significant influence on the financial structure but degree of operating leverage have no significant influence on the financial structure partially. Keywords : sales growth, degree of operating leverage, profitability, financial structure.